III-V compound semiconductor nanowires - Paiman, S; Joyce, H; Kang, J; Gao, Q; Tan, H; Kim, Y; Zhang, X; Zou, J; Jagadish, C (2009)
InP and GaAs based nanowires were grown epitaxially on InP or GaAs (111)B substrates by metalorganic chemical vapor deposition via vapor-liquid-solid (VLS) mechanism. In this report, I will give an overview of nanowire research activities in our group. In particular, the effects of growth parameters for InP and GaAs nanowires on the crystal quality have been studied in detail. We demonstrated the ability to obtain defect-free GaAs nanowires and control the crystal structure of InP nanowires, ie, WZ or ZB, by choosing a combination of growth parameters, such as temperature, V/III ratio and nanowire diameter. © 2009 IEEE NANO Organizers.